2023
DOI: 10.1126/sciadv.adg6319
|View full text |Cite
|
Sign up to set email alerts
|

A whole-genome reference panel of 14,393 individuals for East Asian populations accelerates discovery of rare functional variants

Jaeyong Choi,
Sungjae Kim,
Juhyun Kim
et al.

Abstract: Underrepresentation of non-European (EUR) populations hinders growth of global precision medicine. Resources such as imputation reference panels that match the study population are necessary to find low-frequency variants with substantial effects. We created a reference panel consisting of 14,393 whole-genome sequences including more than 11,000 Asian individuals. Genome-wide association studies were conducted using the reference panel and a population-specific genotype array of 72,298 subjects for eight pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…16 Addressing this could involve leveraging Korean-speci c reference genome data for imputing GWAS results. [34][35][36] Intronic variants emerged as signi cant loci, affecting the splicing of genes like ASIC2 (rs9902778, rs1490895) and SMOC2 (rs2342645). ASICs, responsive to extracellular acidosis, have been implicated in pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Addressing this could involve leveraging Korean-speci c reference genome data for imputing GWAS results. [34][35][36] Intronic variants emerged as signi cant loci, affecting the splicing of genes like ASIC2 (rs9902778, rs1490895) and SMOC2 (rs2342645). ASICs, responsive to extracellular acidosis, have been implicated in pain sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of such datasets from diverse Asian populations presents a unique opportunity for amalgamating multiple WGS datasets into a singular, more comprehensive, and expansive reference panel, which would encapsulate a broader spectrum of genetic diversity, thereby enhancing its utility for human genetic study in Asian populations. The recently published Northeast Asian Reference Database, with over half of the samples deriving from Japan and Korea, represented populations from Northeast Asia (67). In our study, we conducted jointcalling between WBBC-seq and 1kGP-Asian, followed by mutual imputation with SG10K and GAsP to construct the South and East Asian reference Database (SEAD) panel, covering the widest geographical area in Asia, with the majority of its population originating from South and East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of such vast datasets from diverse populations presents a unique opportunity: the combination of multiple WGS datasets to form a more comprehensive and expansive reference panel. The recently published Northeast Asian Reference Database, with over half of the samples deriving from Japan and Korea, represented populations from Northeast Asia(52). In our study, we integrated the data from WBBC with other Asian populations to construct the South and East Asian Reference Database (SEAD) reference panel, covering the widest geographical area in Asia, with the majority of its population originating from South and East Asia.With the SEAD panel, we first assessed the imputation performance across populations at the global scale by using HGDP database.…”
mentioning
confidence: 99%
“…[277][278][279] This suggests that GPR75 inhibition may provide novel therapeutic approaches for T2D and other diseases associated with insulin hypersecretion and resistance. 279 Choi et al 280 similarly found that a missense variant of GPR75 (p.T27A) showed a similar direction of action as the BMI-associated protein truncation variant. According to statistics, about 3 billion people worldwide are currently overweight or suffering from obesity, which shows that there is a broad market for weight loss drugs.…”
Section: Structure and Function Of Gpr75mentioning
confidence: 93%